2019
DOI: 10.1002/chem.201901612
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Guest‐Induced Multimode Photoluminescence Switch for Sequential Logic Gates in a Photoactive Coordination Cage

Abstract: Molecular or supramolecular level photoluminescence (PL) modulation combining chemical and photonic input/output signals together in an integrated system can provide potential high‐density data memorizing and process functions intended for miniaturized devices and machines. Herein, a PL‐responsive supramolecular coordination cage has been demonstrated for complex interactions with redox‐active guests. PL signals of the cage can be switched and modulated by adding or retracting Fc derivatives or converting TTF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…However,addition of TTF into MOC-16 solution gives rise to appearance of EPR signal even under natural sunlight, indicating oxidization of TTF into TTF +C radical. [52] Further addition of TEOAi nto above mixture causes disappearance of EPR signal, suggesting aquenching of TTF +C radical by electron interchange between TTF +C and TEOAs acrificing electron donor. Similar redox events were also observed for TET-TTF and TCN-TTF (Supporting Information, Figure S4).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However,addition of TTF into MOC-16 solution gives rise to appearance of EPR signal even under natural sunlight, indicating oxidization of TTF into TTF +C radical. [52] Further addition of TEOAi nto above mixture causes disappearance of EPR signal, suggesting aquenching of TTF +C radical by electron interchange between TTF +C and TEOAs acrificing electron donor. Similar redox events were also observed for TET-TTF and TCN-TTF (Supporting Information, Figure S4).…”
mentioning
confidence: 97%
“…ThePLquenching of MOC-16 by TTF could be contributed from host-guest electron transfer from TTF to Ru 2+ -based *MOC-16, in which the 3 MLCT excited state is interacted by redox TTF via areductive quenching procedure,while TTF itself is oxidized to TTF + C species. [50] Our previous PL titration study revealed ac irca 20-fold higher static quenching constant (K s ,3 2500 [mol L À1 ] À1 )than the dynamic constant (K c ,1561 [mol L À1 ] À1 ) for MOC-16 + TTF system, [52] suggesting that the PL quenching of MOC-16 by TTF is dominated by formation of hostguest complex, which forms the basis of synergistic coupling effect with TTF guest as photoredox mediator within the confined nanocage.I nc ontrast, TET-TTF/TCN-TTF just quench emission of MOC-16 slightly (Supporting Information, Figure S10), implying ar edox interacting role in bulk solution different from the host-guest system, which is consistent with the EPR results that electron transfer between MOC-16 and TET-TTF/TCN-TTF indeed occurs but the photocatalytic efficiencyisr educed obviously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, addition of TTF into MOC‐16 solution gives rise to appearance of EPR signal even under natural sunlight, indicating oxidization of TTF into TTF +. radical . Further addition of TEOA into above mixture causes disappearance of EPR signal, suggesting a quenching of TTF +.…”
Section: Figurementioning
confidence: 86%
“…species . Our previous PL titration study revealed a circa 20‐fold higher static quenching constant ( K s , 32 500 [mol L −1 ] −1 ) than the dynamic constant ( K c , 1561 [mol L −1 ] −1 ) for MOC‐16+TTF system, suggesting that the PL quenching of MOC‐16 by TTF is dominated by formation of host‐guest complex, which forms the basis of synergistic coupling effect with TTF guest as photoredox mediator within the confined nanocage. In contrast, TET‐TTF/TCN‐TTF just quench emission of MOC‐16 slightly (Supporting Information, Figure S10), implying a redox interacting role in bulk solution different from the host‐guest system, which is consistent with the EPR results that electron transfer between MOC‐16 and TET‐TTF/TCN‐TTF indeed occurs but the photocatalytic efficiency is reduced obviously.…”
Section: Figurementioning
confidence: 97%